Anode Improvement in Rechargeable Lithium–Sulfur Batteries. Issue 48 (19th June 2017) - Tao, Tao; Lu, Shengguo; Fan, Ye; Lei, Weiwei; Huang, Shaoming; Chen, Ying
Abstract: Owing to their theoretical energy density of 2600 Wh kg −1, lithium–sulfur batteries represent a promising future energy storage device to power electric vehicles. However, the practical applications of lithium–sulfur batteries suffer from poor cycle life and low Coulombic efficiency, which is attributed, in part, to the polysulfide shuttle and Li dendrite formation. Suppressing Li dendrite growth, blocking the unfavorable reaction between soluble polysulfides and Li, and improving the safety of Li–S batteries have become very important for the development of high‐performance lithium sulfur batteries. A comprehensive review of various strategies is presented for enhancing the stability of the anode of lithium sulfur batteries, including inserting an interlayer, modifying the separator and electrolytes, employing artificial protection layers, and alternative anodes to replace the Li metal anode. Abstract : Anodes play an important role in resolving the issues of conventional lithium sulfur batteries . The most recent progress in anodes for lithium–sulfur batteries is introduced. To suppress the corrosion reaction that occurs and the formation of Li dendrites on the surface of lithium metal, various strategies are summarized. Employing alternative anodes for sulfur‐based rechargeable batteries is also discussed.